A MARKETING APPROACH FOR THE INTERNET CENTERED ON E-COMMERCE - Yunda Adisa; Muhammad Irwan Padli Nasution; Sri Suci Ayu Sundari (Transpublika Publisher, 2023)
From time to time, the dynamics of business competition in the development of the world of information technology which is increasingly advanced and fast has affected a large part of society, from the simple to the modern and fast, thereby affecting information behavior in all fields, including education, health, entertainment, social resources, information, work, business and communication without space and time limits, the need for faster and cheaper information certainly requires online media from information providers, where information consumers can easily and quickly obtain the information presented. This research was conducted to find out everything related to the internet and e-commerce. This research method uses primary and secondary data from books, social media and websites. From the findings of this study, there are weaknesses in human resources in terms of e-commerce knowledge, so they cannot make full use of e-commerce.